Inclusive Special School Teachers’ Self-Assessment of their Diagnostic and Therapeutic Knowledge and Skills - BORZĘCKA, ANNA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Anna Borzęcka, Inclusive Special School Teachers’ Self-Assessment of their Diagnostic and Therapeutic Knowledge and Skills. Interdisciplinary Contexts of Special Pedagogy, no. 27, Poznań 2019. Pp. 181–195. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.27.09 Diagnostic and therapeutic competences are necessary for the effectiveness of didactic and educational interventions undertaken by a professional specialist school teacher. In order for the teacher to be able to cope with the tasks assigned by special pedagogy, he must have theoretical and practical preparation in the field of diagnosis and therapy. The future of a special school pupil will depend on his knowledge and skills. The article presents research on declarative sources of teaching knowledge and skills in the field of diagnosis and therapy as well as their selfassessment, taking into account nominal variables (age and job seniority).